2013
DOI: 10.1080/13691457.2013.806295
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers of the elderly: quality of life and coping in Estonia

Abstract: The purpose of the study was to analyse the assessments of elderly people aged 65 and more about family caregiving as a factor influencing their quality of life and coping. The study is based on the project SUFACARE*'Supporting family carers and care receivers in Estonia and in Finland'*in the framework of which the Institute of Social Work of Tallinn University carried out postal surveys in 2010. The Estonian survey was conducted in Tallinn and Lääne-Viru County. The total number of respondents was 581 (70% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…1 The elderly reap joy from their families and children. 2 Most elderly seek happiness in their homes, being surrounded by their children and grandchildren. 3 Investigations in diverse contexts reveal that the elderly fancy living in their own homes and communities.…”
Section: Introductionmentioning
confidence: 99%
“…1 The elderly reap joy from their families and children. 2 Most elderly seek happiness in their homes, being surrounded by their children and grandchildren. 3 Investigations in diverse contexts reveal that the elderly fancy living in their own homes and communities.…”
Section: Introductionmentioning
confidence: 99%
“…Lin, Chen, and Li 23 ) suggested that the quality of the relationship between the caregiver and the care recipient is an important factor influencing caregiver’s behavior and caregiving. Another study suggested that the negative effects of caregiving included feelings of isolation 24 ) , financial problems 12 ) , and relationship problems at home 25 ) . Therefore, understanding factors such as fulfillment from the caregiving role, quality of the relationship, feelings of isolation, and relationship problems at home are important when interpreting caregiving situations.…”
Section: Introductionmentioning
confidence: 99%